Mucosal IL-10 and TGF-β play crucial roles in preventing LPS-driven, IFN-γ–mediated epithelial damage in human colon explants - Jarry, Anne (American Society for Clinical Investigation, 2008)
IL-10 is an immunomodulatory cytokine that plays an obligate role in preventing spontaneous enterocolitis in mice. However, little is known about IL-10 function in the human intestinal mucosa. We showed here that IL-10 was constitutively expressed and secreted by the human normal colonic mucosa, including epithelial cells. Depletion of IL-10 in mucosal explants induced both downregulation of the IL-10–inducible, immunosuppressive gene BCL3 and upregulation of IFN-γ, TNF-α, and IL-17. Interestingly, TGF-β blockade also strongly induced IFN-γ production. In addition, the high levels of IFN-γ produced upon IL-10 depletion were responsible for surface epithelium damage and crypt loss, mainly by apoptosis. Polymyxin B, used as a scavenger of endogenous LPS, abolished both IFN-γ production and epithelial barrier disruption. Finally, adding a commensal bacteria strain to mucosa explant cultures depleted of both IL-10 and LPS reproduced the ability of endogenous LPS to induce IFN-γ secretion. These findings demonstrate that IL-10 ablation leads to an endogenous IFN-γ–mediated inflammatory response via LPS from commensal bacteria in the human colonic mucosa. We also found that both IL-10 and TGF-β play crucial roles in maintaining human colonic mucosa homeostasis.